By Community Assistance On The Development Of Salt Farmers In Jeneponto Regency - ST. Arphina Bahar; St. Aisyah BM (Universitas Islam Negeri Alauddin Makassar, 2022)
Community assistance in an effort to develop salt farmers' businesses lies in the concept of community assistance that is applied. This type of research is a qualitative research that uses descriptive analysis method where empowerment in this research is carried out through a sociological approach from various series of activities such as observation, interviews and documentation. And supported by various sources of primary data and secondary data. The results of this study indicate that: 1) Community assistance strategies in efforts to develop salt farmers' businesses in Jeneponto district are broadly divided into four aspects, namely cooperation between the sub-district government and farmer groups, strengthening capital and human resources, developing marketing, and strengthening potential salt farming. 2) The impact of community assistance by farmer groups in the effort to develop salt farmers' businesses in Jeneponto district, salt farmers are able to grow and develop more independent salt farmer groups, the development of human resources, one of which is in terms of knowledge, but in terms of technological capabilities and increasing economic level not running optimally.